Finite elastic wrinkling deformations of incompressible fiber-reinforced plates - Taylor, M. (Int J Eng Sci, 2019)
A two-dimensional plate theory, valid for finite elastic deformations with small strains, is derived for incompressible, fiber-reinforced materials. Single-layer plates and two-layer laminates are considered. Numerical simulations illustrate the substantial effect that fiber reinforcement has on wrinkling patterns in the sheet.